MOTIVATION OF ELDERLY WOMEN TO RECREATE RECREATIONAL AND HEALTH ACTIVITIES AS A NEED TO SATISFY LIFE - Дудіцька, Світлана; Vaskan, Ivan; Khudytska, Khrystyna (Науковий часопис Національного педагогічного університету імені М.П. Драгоманова, 2021)
Maintaining health and the emotional component on a part with physical factors affects the life expectancy and satisfaction of older women. To increase the level of physical and psychological health of elderly women, it is necessary to increase the amount of physical activity, various interesting and effective forms of recreational activities, because exercise, hard work also bring life satisfaction. Therefore, the motivating factors for recreational and health-improving physical activity, which influences the improvement of health and life satisfaction of elderly women, play an important role. The purpose of our study is to examine the motives for recreational and health motor activity of elderly women. Methods and organization of research. In the course of the research we used the following methods: analysis of literature sources, method of sociological survey (questionnaire), methods of determining life satisfaction (Scale of life satisfaction of E. Diner, methods of mathematical statistics). 39 respondents, aged 60-75, took part in the Chernivtsi Municipal Territorial Center for Social Services "Care". Results. We have identified the main motives for recreational and health activities, identified what motivates these people to engage in recreational and health activities, identified the main reasons that hinder physical activity, identified priority types of recreational and recreational activities for older women.
Keywords: motivation, recreational and health-improving activity, elderly women